Advanced thermoforming : methods, machines and materials, applications and automation - Engelmann, Sven (Wiley, 2012)
"Introduces the latest innovations in thermoforming materials, processes, and applicationsAdvanced Thermoforming brings readers fully up to date with the latest standards, processes, materials, and applications in the field. From forming to filling to sealing processes, the author explains everything that can now be accomplished using the most advanced thermoforming technologies available. Moreover, readers learn how to fully leverage these technologies in order to design and manufacture products that meet all specifications at minimum cost and maximum efficiency."--Resumé vydavatele
Terminologický slovník
Keywords: tváření plastů; plasty; tváření za tepla; plastics; plastic moulding; hot working; příručky; elektronické knihy; handbooks and manuals; electronic books